The QUBIC instrument for CMB polarization measurements. (May 2020) - Mele, L; Ade, P; Alberro, J G; Almela, A; Amico, G; Arnaldi, L H; Auguste, D; Aumont, J; Azzoni, S; Banfi, S; Battistelli, E S; Baù, A; et al.
Abstract: Measurements of cosmic microwave background (CMB) polarization may reveal the presence of a background of gravitational waves produced during cosmic inflation, providing thus a test of inflationary models. The Q&U Bolometric Interferometer for Cosmology (QUBIC) is an experiment designed to measure the CMB polarization. It is based on the novel concept of bolometric interferometry, which combines the sensitivity of bolometric detectors with the properties of beam synthesis and control of calibration offered by interferometers. To modulate and extract the input polarized signal of the CMB, QUBIC exploits Stokes polarimetry based on a rotating half-wave plate (HWP). In this work, we illustrate the design of the QUBIC instrument, focusing on the polarization modulation system, and we present preliminary results of beam calibrations and the performance of the HWP rotator at 300 K.